Uma análise da contribuiç\~ao do Fundeb sobre a qualidade da educaç\~ao pública dos municípios brasileiros - Kalinca Léia Becker (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This study analyzed the effect of Fundeb on the Saeb results of the municipalities by estimating a spatial panel model with information from 2007 and 2017, which contemplates the 10 years of the fund's implementation. The results indicated that the increase of 10% in the Fundeb amount per student received by the municipality raised the Saeb score by approximately one point. The increase of the amount in neighboring municipalities, in turn, contributed to increase the municipality's Saeb score by approximately three points. These results are evidence in favor of the hypothesis that Fundeb promote the management and adoption of good practices in municipal education, which influence the decisions and behavior of managers in neighboring municipalities to also improve their practices and results.
Keywords: I28; H75; C21; 330; education; public spending; proficiency